Road pricing from a geographical perspective: a literature review and implications for research into accessibility - Taede Tillema; Bert Van Wee; Tom De Jong (European Regional Science Association (ERSA), 2003)
Road pricing policies have been a subject of research for many decades. Even though until now examples of actual implication in the real world are limited, many different road-pricing measures have been considered, both in literature as well as in the political debate in several countries. However, most literature focuses on economic aspects, more or less ignoring spatial consequences. In this paper we will concentrate on the spatial effects of pricing policy and introduce the typical geographic concept of accessibility into the discussion about pricing policy. The paper firstly gives some backgrounds of pricing policies. Some objectives of road pricing in general are given. Furthermore some examples of already implemented pricing measures in countries all over the world are mentioned. General literature concerning pricing policies aims specifically on economic effects. This is mainly because of the typical economic aspects, which can be found in the theory of pricing policy such as the pricing of a scarce good as infrastructure capacity, related to time aspects. Also studies concerning acceptability of road pricing policies are discussed, because acceptance plays an important role in the implementation of pricing policies. The paper shortly addresses some of the economic and acceptability related literature. But the literature review of the paper focuses specifically on the geographical aspects of pricing policies. These geographical aspects have received much less attention so far although road-pricing measures may cause important spatial effects. Therefore the second part of the paper focuses on these geographical aspects. A specific research field in geography is accessibility. Accessibility is a concept that connects infrastructure and land-use. The research fields of accessibility and pricing policies in isolation are well elaborated. However, the link between road pricing policies and accessibility (measures) forms a new research field. The paper explains the importance of the concept of accessibility. In practice accessibility can be computed with accessibility measures. These measures form quantifications of accessibility. Different types of accessibility measures exist differing in concept as well as complexity. All these measures have in common that transport costs are not included at all or at least not in a realistic way. After explaining the concept of accessibility different categories of accessibility measures are explained and their general advantages and disadvantages are given. Furthermore possibilities to adapt or improve accessibility measures are discussed. After this discussion the actual link between road pricing policies and accessibility measures is explained. The discussion begins with the presentation of a conceptual model of the accessibility (and spatial) effects of road pricing. Subsequently an observation is made where current measures fall short to include pricing policy costs in a realistic way. This observation will lead to the determination of directions for improvement. Besides the general possibilities to adjust different accessibility measures, each measure is specifically evaluated on the ability to improve the way of describing accessibility effects of road pricing.
Keywords: 330